Influence of Children’s Motor Development Primary School Age in the Learning Process - Arqiya, Safiya; Khairunnisa Ramadani, Cut (International Journal of Students Education, 2023)
Motor skills are abilities related to body movements whose development is influenced by age and overall development. Motor skills also occur in a system commonly called sensory motor. Motor processes occur physiologically which influence muscle contractions so that they can cause movements that occur in humans. This motor ability plays an important role in carrying out an activity so that it can run well, as well as in the learning process, this motor ability is very much needed in student activity in the classroom. Capture ability in understanding in learning and responding to stimuli given by the teacher so that students are important. in studying it. Physical growth and development is related to the physical motor development of children. Through children’s unique characteristics, namely great curiosity and the desire to try, children can carry out physical motor exercises through coordinated movements that are facilitated by a supportive environment that provides stimulation. Another development that is also related to a child’s motor skills is that the child will be quicker to react, the better his eye and hand coordination will be, and the child will be more agile in moving. As children’s self-confidence increases, children will also feel proud if they can do several activities. With these motor skills, children will be able to play together with their friends, such as jumping, running, circling their arms, and so on. Apart from that, good motor skills are also characterized by the child’s fast motor reactions, better coordination and cooperation. To train children’s motor development, it is best to provide stimulation continuously, meaning that it does not stop at just one stimulus because it is not certain that they can immediately master one stimulus, there are many types of movement elements that children must master in their motor development.